2021
DOI: 10.1002/ange.202017318
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Self‐Assembly of a Giant Heterometallic Polyoxotungstate Supercluster with Antitumor Activity

Abstract: The hierarchical aggregation of molecular nanostructures from multiple components is a grand synthetic challenge, which requires highly selective linkage control. We demonstrate how two orthogonal linkage groups, that is, organotin and lanthanide cations, can be used to drive the aggregation of a giant molecular metal oxide superstructure. The title compound {[(Sn(CH 3 ) 2 ) 2 O] 4 {[CeW 5 O 18 ] [TeW 4 O 16 ]-[CeSn(CH 3 ) 2 ] 4 [TeW 8 O 31 ] 4 } 2 } 46À (1 a) features dimensions of ca. 2.2 2.3 3.4 nm 3 and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, several previous studies reported that the oral administration of POMs is presumed safe with a low risk of negative health effects. , For instance, polyoxotungstates show a potential antitumor activity and lower toxicity in vitro as well as in vivo experiments . Especially, vanadotungstates and polyoxovanadates have evidenced a good antitumor activity against some human cancer cells (MCF-7 human breast cells, HepG2 hepatocellular carcinoma cell, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several previous studies reported that the oral administration of POMs is presumed safe with a low risk of negative health effects. , For instance, polyoxotungstates show a potential antitumor activity and lower toxicity in vitro as well as in vivo experiments . Especially, vanadotungstates and polyoxovanadates have evidenced a good antitumor activity against some human cancer cells (MCF-7 human breast cells, HepG2 hepatocellular carcinoma cell, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…The unique properties of POMs with various sizes, shapes, and high negative charges could enable the POM-based MOFs to exhibit adjustable porous sizes. , In addition, besides their structural advantages, POMs allow chemical and structural modifications at a molecular level and can carry out reversible, fast, and multistep electron-transfer reactions without changing their structures. , Therefore, POM-encapsulated MOFs have emerged as a new family of multifunctional hybrids that includes two key research fields: MOFs and POMs. One of the first proposed applications of POM-encapsulated MOFs is in heterogeneous catalysis, and thus, recently, such materials have made significant contributions to fields such as photo- and electrocatalysis. Nevertheless, very few examples of POM-encapsulated MOFs have been reported because the assembly of such MOFs is still a significant synthetic challenge. Organic ligands are key synthons to obtain the desired MOF skeleton . Mixed-ligand MOFs have more advantages than single-ligand ones, as a high level of practical molecular design and the potential synergetic coordinated interactions of distinct ligands with metals result in novel POM-encapsulated MOFs .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the crucial role of multiple intermediates adsorption over the electrocatalyst's surface/interfaces, more attention should be paid to creating multi-active sites in one catalytic material like high-entropy alloys to collaboratively optimize their interaction with different intermediates during 2e-WOR. [128][129][130][131][132][133][134] Recent years have witnessed a surge of interest in restructuring and strain engineering of nanocatalysts for electrocatalytic applications with improved activities including hydrogen evolution, oxygen reduction, and oxygen evolution, which may be extendable for 2e-WOR catalysts. [135,136] To promote mass transfer, tailoring the morphology of the catalysts with 3D hierarchically open porous architectures can effectively increase the availability of active sites and accelerate the diffusion of relevant species.…”
Section: Discussionmentioning
confidence: 99%